Henderson, the rain king - Bellow, Saul. (London : Penguin Books, 2007)
Henderson, a middle-aged American millionaire, travels to Africa in search of a more rewarding life, and finds himself regarded as a messiah when he manages to bring rain to a drought-stricken tribe.
Young Adult.
Young Adult
Keywords: Americans -- Travel -- Africa -- Fiction; Americans -- Travel -- Fiction; Fables; Humorous fiction; Africa -- Fiction; Africa -- Fiction; Fables; Humorous stories